Assessing Medication Adherence Among Patients With Diabetis Mellitus Attending The Diabetes Clinic At Kintampo Municipal Hospital - Seidu, H. (University Of Ghana, 2021)
Abstract Introduction: Globally, adults with type 2 diabetes struggle adhering to anti-diabetes medication. Thirty-three percent of people living with diabetes are non-adherent to their prescribed medication. Medication adherence among patients with diabetes mellitus is undocumented in the Kintampo Municipal thus affecting diabetes care. This study examined medication adherence among patients with diabetes attending the diabetes clinic at the Kintampo Municipal Hospital. Methods: This was a quantitative cross-sectional study of 248 patients with diabetes. Systematic random sampling was used to select the participants. A structured questionnaire and Morisky’s Medication Adherence Scale-8 were used. STATA version 16.0 was used to perform the analysis. A Chi-square test was used to determine the association between medication adherence and the independent factors. Ordinal logistic regression analysis was done to assess the degree of association. Results: Of the 248 participants, 146 (58.9%) were males. The mean age was 57.9 ± 11.8 years. Majority of the respondents 121 (48.8%) were 60 and above years. The prevalence of medication adherence among patients with diabetes was 5.6% (95% C.I 3.4% - 9.3). In multiple ordinal regression, knowledge of the type of diabetes medication (aOR=0.16 95% CI=0.03 - 0.65) was significantly associated with medication adherence. Conclusion: The prevalence of medication adherence is low. Knowledge of the type of medication decreases the odds of adherence. Targeted diabetes counseling and education in diabetes clinics may increase medication adherence.
MPH
Keywords: Kintampo; Hospital; Diabetis; Mellitus; Clinic